A Study on Production of Poly-β-Hydroxybutyrate Bioplastic from Sago Starch by Indigenous Amylolytic Bacteria - Nur Arfa Yanti; Langkah Sembiring; Sebastian Margino; Nurhayani H. Muhiddin (Indonesian Journal of Biotechnology, 2013)
Bacillus sp. PSA10 and Bacillus sp. PPK5 were two indigenous strain amylolytic bacteria from SoutheastSulawesi that have ability to produce bioplastic poly-β-hydroxybutyrate (PHB) from sago starch. The study wasattempted to determine the mechanism of PHB production by bacteria amylolytic was grown on sago starchcontainingmedia. Two amylolytic bacteria i.e. Bacillus sp. PSA10 and Bacillus sp. PPK5 was grown for 168 hin a mineral salts medium with sago starch as carbon source. Growth of amylolytic bacteria was monitoredby cell dry weight. Extraction of PHB was done by N-hexane acetone-diethyl ether method and PHB contentwas quantifi ed with UV spectrophotometer at 235 nm. Glucose level was determined by using kit of glucoseGOD 10” and was quantifi ed with spectrophotometer at 500 nm. Sago starch concentration was determinedby phenol method using specthrophotometer at 490 nm. The result of the study showed that Bacillus sp.PSA10 was produced PHB up to 66,81 % (g PHB/g cell dry weight) at 48 h and Bacillus sp. PPK5 up to 24,83% (g PHB/g cell dry weight) at 84 h. Bacillus sp. PSA10 has ability to converse sago starch to be PHB directlywithout glucose accumulation in the media, whereas Bacillus sp. PPK5 have to accumulate glucose as productof sago starch hydrolysis to produce of PHB. PHB synthesis by Bacillus sp. PHB production on sago starchof the Bacillus sp. PSA10 was found to be growth-associated whereas Bacillus sp. PPK5 was found to be nongrowth-associated. Therefore, two indigenous amylolytic bacteria were having of difference in biosynthesismechanism of PHB in sago starch medium and their characteristics of PHB synthesis should be consideredin developing cultivation methods for the effi cient production of PHB. Keywords : Production, PHB, Amylolytic bacteria, Sago starch.